Análise de contaminação em solo e água subterrânea por hidrocarbonetos derivados de petróleo - Vivian, Rafael Bitencourt (2015)
This research aimed to delineate the contamination plume, coming from a leak in the fuel station dealer, penetrating crystalline aquifer in the Rio Grande do Sul state southern Brazil. Determined with the use of a steam THERMO GASTECH Analyzer, model Innova SV, were measured in situ concentrations of volatile organic compounds (VOC) in soils. For the identification of hydrocarbons in free phase (portion of supernatant contaminants in groundwater). Was employed a digital level meter model HSIFD-30, which allowed the detection of fluids (contaminants) in free phase using probe that measures the water and oily fluid interface. The heterotrophic bacteria count and identification of the groundwater, to verify the existence of autochthonous microbiota with ability to degrade hydrocarbons derived from oil. As a result, were mapped and determined the concentrations of TPH plume contamination in form of VOCs every 0.5 m deep, reaching up to 3.5 m in deep. The largest concentrations of VOCs, occurred in the depths of 2.5; 3.0 and 3.5 m, where concentrations were above 10.000 ppm, even to register 100% LEL, limit of detection equipment. As the free phase, mapped a plume of contamination supernatant in groundwater with thicknesses ranging from 2 to 5 mm. Both vapour and free phase plumes, already surpassed the physical limits of the enterprise reaching existing residential and commercial areas to the North direction. The existence of microorganisms were identified species-degrading Pseudomonas aeruginosa, Bacillus sp., Burkholderia glandioli, Pseudomonas sp. and Acinetobacter sp. both species considered by several authors such as hydrocarbon degrading. The identification of the contaminated area and the study of the interactions of these compounds with the medium are of the utmost importance to the development of strategies and technologies aimed at their recovery.